The Uterine Tube: From Herophilus to Horacio Croxatto [la Tuba Uterina: Desde Herófilo a Horacio Croxatto] - Osses-Mc Intyre, M; Orihuela-Diaz, P; Godoy-Guzman, C (Universidad de la Frontera, 2018)
The uterine tubes (UT) are fundamental tubular organs in human reproduction. However, it was not until the middle of the 17th century that Reinier De Graaf s research began to reveal its true role in reproduction. In this work the main contributions of Horacio Croxatto Avoni toward the knowledge of the morphology and physiology of the human UT are summarized. Its main contributions are related to the physiology of zygote transport and gametes throughout the UT. © 2018, Universidad de la Frontera. All rights reserved.